1999
DOI: 10.3171/foc.1999.7.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the pathophysiology of syringomyelia

Abstract: Object Syringomyelia causes progressive myelopathy. Most patients with syringomyelia have a Chiari I malformation of the cerebellar tonsils. Determination of the pathophysiological mechanisms underlying the progression of syringomyelia associated with the Chiari I malformation should improve strategies to halt progression of myelopathy. Methods The authors prospectively studied 20 adult patients with bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
147
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(159 citation statements)
references
References 15 publications
7
147
0
5
Order By: Relevance
“…The optimal surgical management to eliminate this mechanism and to reduce the syrinx was proposed to be a procedure that could expand the CSF pathway at the foramen magnum: posterior fossa decompression, upper cervical laminectomy and augmenting duraplasty. 1 Phase contrast cine-MRI made it possible to evaluate the altered cerebrospinal¯uid dynamics in patients with Chiari I malformations. Postoperative changes in CSF¯ow pro®les included an increase in velocity magnitude and a change in the direction of¯ow from a previously constricted posterior fossa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal surgical management to eliminate this mechanism and to reduce the syrinx was proposed to be a procedure that could expand the CSF pathway at the foramen magnum: posterior fossa decompression, upper cervical laminectomy and augmenting duraplasty. 1 Phase contrast cine-MRI made it possible to evaluate the altered cerebrospinal¯uid dynamics in patients with Chiari I malformations. Postoperative changes in CSF¯ow pro®les included an increase in velocity magnitude and a change in the direction of¯ow from a previously constricted posterior fossa.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical repositioning of the tonsil, normalization of abnormal CSF¯ow pro®les after foramen magnum decompression or decompression of syrinx itself might explain the clinical improvement of the patients. 1 In the syringomyelia other than Chiari malformation, a similar but simpler concept is applied as there is no tonsillar herniation or complicating mechanism of syrinx propagation associated with it. There remains CSF¯ow obstruction and pathological change to the subarachnoid space, such as arachnoid adhesion or Figure 2 (a) T1-weighted sagittal view of thoraco-lumbar MRI shows the extent of syringomyelia to be di use, from upper thoracic to conus level (small arrows) with interruption at T9 to T12 level which is also the previous operation site (large arrows).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, however, some authors 19,20 using X-ray, computed tomography and magnetic resonance imaging (MRI) examinations have also demonstrated that the posterior fossa volume, in the presence of BI and CM, is smaller than those observed in normal people. Milhorat et al 21 verified a decrease of 13.4 mL in the total volume of the posterior fossa and 40% (10.8 mL) in the CSF volume of this region.…”
Section: Discussionmentioning
confidence: 99%
“…Basic to all the procedures is enlargement of the foramen magnum with the intent of establishing relatively unimpeded flow of CSF from the cranial cavity to the spinal subarachnoid space. [5][6][7][8][9] In the present study, we review our experience with the treatment of CM1 in patients who underwent decompression with or without duraplasty and the correlation of clinical and imaging outcomes after 2 year of follow up.…”
Section: Introductionmentioning
confidence: 99%